Environmental Sustainability in Action: Student Narratives on Practicing Green Habits beyond the Classroom - Ahasmarie Pasion-Pasinabo (Journal of Daoist Studies, 2026)
This qualitative study explored how college students from Zamboanga Peninsula, Philippines, who are members of environmental-related organizations, narrate their lived experiences in applying sustainability practices in real-life contexts. It also examined their motivations, challenges, and strategies in maintaining these habits beyond academic requirements. Through in-depth interviews with sixteen purposively selected college students, the research found that sustainable behaviors are driven by deeply internalized values, reinforced by classroom learning, and supported by social and community influences. Themes such as the conscious reduction of single-use plastics, lifestyle shifts toward zero-waste and plant-based living, and the use of proactive strategies for habit formation emerged. Despite challenges like limited access to resources and peer pressure, students sustained their efforts through personal commitment, peer accountability, and future-oriented thinking. This study emphasizes that environmental education must extend beyond awareness to foster identity formation, community support, and systemic access to sustainable choices.